Eksperimental Pengaruh Variasi Sudut Ulir Pada Turbin Ulir (Archimedean Screw) Pusat Pembangkit Listrik Tenaga Mikro Hidro Dengan Head Rendah - Saputra, Agus Trisna; Weking, Antonius Ibi; Artawijaya, I Wayan (Majalah Ilmiah Teknologi Elektro; Vol 18 No 1 (2019): (Januari - April) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i01.P12, 2019)
Indonesia has a lot of energy potential, both conventional (Non Renewable) and Renewable Energy. Energy potential that is mostly used for the Indonesian region still uses conventional energy (Non Renewable) in the form of fossil fuels (coal, natural gas and petroleum). At present, fossil energy use reaches 75% and will continue to increase. To avoid the use of fossil energy, studies are carried out on renewable energy (Non Renewable) for example Micro Hydro. The working principle of the Micro Hydro Power Plant use the potential energy of water which is converted into electrical energy. In this final project research has been made modeling of micro hydro power plants using screw turbines (Archimedean Screw) with tubrine blade angle variations ranging from 24 0 , 26 0 ,28 0 ,30 0 and 32 0 . The measurements made in this study include measurement of turbine rotation, generator rotation, voltage, current and torque generated in the modeling that has been made. From the measurements that have been made using a lamp load of 25 Watts the highest measurement results are obtained at an angle of 28 0 . At an angle of 28 0 produces a power of 10.8 Watts, torque of 0.33 Nm and efficiency of 11.6%.